Porewater geochemistry of sediment core AL561_20-1 - Andy W Dale; Ulrike Lomnitz (PANGAEA, 2025)
The AL561 cruise was conducted in the framework of the project APOC ("Anthropogenic impacts on Particulate Organic Carbon cycling in the North Sea"). This collaborative project between GEOMAR, AWI, HEREON, UHH, and BUND is to understand how particulate organic carbon (POC) cycling contributes to carbon sequestration in the North Sea and how this ecosystem service is compromised and interlinked with global change and a range of human pressures include fisheries (pelagic fisheries, bottom trawling), resource extraction (sand mining), sediment management (dredging and disposal of dredged sediments) and eutrophication. The main aim of the sampling activity during AL561 cruise was to recover undisturbed sediment from high accumulation sites in the Skagerrak/Kattegat and to subsample sediment/porewater at high resolution in order to investigate sedimentation transport processes, origin of sediment/POC and mineralization processes over the last 100- 200 years. Moreover, the actual processes of sedimentation and POC degradation in the water column and benthic layer will be addressed by sampling with CTD and Lander devices. In total 9 hydroacoustic surveys (59 profiles), 4 Gravity Corer, 7 Multicorer, 3 BIGO Lander and 3 CTD stations were successfully conducted during the AL561 cruise.